Posisi Duduk dan Keluhan Nyeri Punggung Bawah Pada Kurir Pengantar Barang di Kota Tanjungpinang : Sitting Position and Complaints of Lower Back Pain in Couriers Delivering Goods in Tanjungpinang City - febe, febe ferdianti natalia; Pitriyanti, Luh; Yusuf.MF (JURNAL ILMU DAN TEKNOLOGI KESEHATAN TERPADU, 2022)
Lower back pain is a sensation in the lower back refers to pain in the area between the lower ribs and above the legs, pain, and pain in the lower back resulting from injury or muscle tension, or it can also be caused by more specific conditions, such as Herniated Disc and also due to overcrowding of activities. The purpose of the study was to find out the characteristics of respondents, sitting position, and the prevalence of back pain complaints that in respondents. The study was descriptive study by conducting interviews using Nordic Body Map (NBM) to determine lower back pain complaints and questionnaires to find out the characteristics and duration of work of respondents and Rapid Entire Body Assessment (REBA) to determine the sitting position. Delivery courier respondents who experienced back pain as many as 17 people (73.9%), sitting position respondents with a sitting position more likely to go forward as many as 13 respondents (56.5%), and respondents who sat upright as many as 10 respondents (43.3%). Advice for respondents is expected to do small stretching movements everyday after work to reduce lower back pain.